Total body water and extracellular water measurements through in vivo dilution of D2O and bromide as tracers. Issue 2 (2003) - Sergi Sergi, Giuseppe Giuseppe; Bertani Bertani, Roberta Roberta; Calliari Calliari, Irene Irene; Lupoli Lupoli, Lucia Lucia; Berton Berton, Adriano Adriano; Volpato Volpato, Stefania Stefania; Enzi Enzi, Giuliano Giuliano
Abstract : Large interest is into the determination of body fluids because of changes in body water in a wide variety of physiological and pathological conditions. Here methods based on dilution of tracers, are reported, for the extracellular water (ECW) and total body water (TBW) determinations on the same sample. As for ECW, bromide is used as tracer and its concentration is determined by energy dispersive X-ray spectrometry; while as for TBW, D2 O is used as tracer and HOD is determined by FT IR. Both methods represent significant improvements with respect the procedures described in the literature in terms of availability, reproducibility and accuracy.